(untitled) (Research, Society and Development, 2021)
Existential Logotherapy and Analysis is impacting on the humanization of education, the theoretical assumption of psychoanalyst Viktor Emil Frankl. It is intended to present the importance of Frankl’s thoughts in the humanization of technology education, which can be changed into actions for a lifestyle in university teaching, research and extension that is a way of prioritizing being over having ( technology, knowing things), being with others, empathizing with others. The purpose of the article is to use the theoretical assumptions of Logotherapy, presenting ways that can raise awareness of the educator-student relationship that can grow in dialogue and more engagement in the pursuit of humanization of relations within university institutions, especially in the case study here that is from the technology area (engineering, architecture, technologies), seeking ways to minimize the existential void of our students, which results in an increase in the phenomena of aggression, crime, drug addiction, depression and reaching the limit of suicide, which has been increasing greatly in the last years.